SINERGITAS PERAN KOMITE DAN KEPALA MADRASAH DALAM MENINGKAT MUTU PENDIDIKAN DI MAN 1 LEBONG, BENGKULU: indonesia - Fahmi Rozi; Nuzuar; Kusen; Idi Warsah (STIT PRINGSEWU, 2020)
This study aimed at exploring information with respect to the extent of the role of Madrasah committee together with the principal in improving the educational quality of MAN 1 in Lebong. This study applied a qualitative approach with observation, interviews, and documentation as the tools of collecting data related to the committee’s performances in carrying out its role. After the data were obtained, the data were processed until the answers in accordance with the research objectives were found. The conclusion of this study revealed that the Madrasah committee had synergized with the principal in carrying out its role as a provider of consideration, supporter, controller, and mediator. However, besides the performances having been undertaken, there were still found a number of TUSI indicators having not been carried out maximally, and the Madrasah committee had not designed the working map of each committee member as well as did not have a planned working program. The performances carried out by the committee were an individual initiative and the result of coordination as well as Madrasah principal’s instruction.